Impacto do uso do solo em comunidades de insetos aquáticos (ephemeroptera, plecoptera e trichoptera) em riachos no bioma Pampa brasileiro - Barreto, Tainara Rosa Menna (2024)
The biodiversity of freshwater ecosystems is drastically decreasing, especially due to the expansion and intensification of agricultural activities. The Brazilian Pampa has been experiencing extensive conversion of grassland areas into agricultural crops, which is responsible for the ecological degradation of several watercourses worldwide, altering community structures and threatening biodiversity. We investigated the impact of land use on the structure of Ephemeroptera, Plecoptera, and Trichoptera (EPT) communities in streams in native grassland with livestock and agricultural cultivation in six grassland formations in the Brazilian Pampa Biome: "barba-de-bode" grassland; shallow soil grassland; interior sub-montane grassland; grassy grassland; shrubby grassland; and Atlantic sub-montane grassland. For each ecosystem, three streams in native grassland with livestock and three streams in agricultural cultivation were selected. EPT immatures were collected using a Surber sampler (10x10cm, 250 μm mesh), as well as local environmental descriptors and soil cover descriptors. The data matrix comprised 30,026 EPT individuals distributed among 16 families and 36 genera. Of these, 22,477 specimens were from native grassland streams and 7,549 were from agricultural cultivation, thar represent a 70% loss in EPT abundance, highlighting the influence of disparities in land use. The genera that most contributed to the difference between land uses were: Smicridea (14.6%), Americabaetis (13.9%), Traverhyphes (10.6%), Farrodes (6.8%), and Chimarra (6.3%). Community structure differed between land uses and grassland ecosystems, and there was interaction between these factors, demonstrating that the impact of land use is not homogeneous among grassland ecosystems. The multivariate variability in community structure was mainly explained by local environmental descriptors (electrical conductivity, water velocity, percentage of sand mesohabitat in the riffle, and vegetation cover). Thus, our hypothesis that the conversion of native habitat into agricultural land exerts a substantial impact on EPT communities in streams within the Pampa biome has been corroborated. Our results suggest that changes in land use and the characteristics of grassland ecosystems have important implications for the ecology and biodiversity of streams in the Pampa biome. Therefore, monitoring through aquatic insect communities represents a valuable tool in assessing the adverse effects stemming from land use conversion in streams within the Brazilian Pampa biome.